My friend the monster - Taylor, Eleanor, 1969- (Bloomsbury Children's Books : Distributed to the trade by Holtzbrinck Publishers, 2008)
After his family moves into their new house, Louis the fox discovers a very frightened monster living under his bed, and when he takes the monster to the park with him, the monster helps him make new friends.